2021
DOI: 10.1177/01614681211058971
|View full text |Cite
|
Sign up to set email alerts
|

Discussion in Diverse Middle School Social Studies Classrooms: Promoting All Students’ Participation in the Disciplinary Work of Inquiry

Abstract: Background/Context: Although calls for rich discussion and argumentation about disciplinary texts and content are frequent, research indicates that in classrooms such discussions are rare. When discussions do happen, few students tend to participate. Purpose/Focus of Study: We look to exemplar teachers’ classrooms where a range of ethnically, racially, linguistically, and academically diverse students participated substantively in discussions throughout social studies inquiries to understand what those teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Teachers hypothesized that students without an elbow partner did not participate in whole group discussions as much as students who had an elbow partner. This point is consistent with findings of our previous research in inquiry-focused classrooms (Monte-Sano et al, 2021). Teachers talked about what they could do differently in the afternoon co-teaching classrooms to support broader student participation (see Figure 4 for discussion excerpts).…”
Section: Debriefing the Seventh-grade Hammurabi Lessonsupporting
confidence: 89%
“…Teachers hypothesized that students without an elbow partner did not participate in whole group discussions as much as students who had an elbow partner. This point is consistent with findings of our previous research in inquiry-focused classrooms (Monte-Sano et al, 2021). Teachers talked about what they could do differently in the afternoon co-teaching classrooms to support broader student participation (see Figure 4 for discussion excerpts).…”
Section: Debriefing the Seventh-grade Hammurabi Lessonsupporting
confidence: 89%
“…It stands to reason, then, that students who learn to use sourcing when analyzing historical evidence found in a diary entry, a letter, a photograph, a movie clip, a novel, a written newspaper account, an online newspaper account, a tweet, and a website might be better prepared to engage in sourcing on their own when studying a current event using a webpage or social media. And current research has shown that such is true when accompanied by class discussion (Monte-Sano et al, 2021). Wineburg and Reisman (2015) expressed their expectation that young people’s internalization of sourcing could be life changing.…”
Section: Applying Historical Argumentation Strategies In Informed Civ...mentioning
confidence: 92%
“…The value of the ADI has also been explored by De La Paz et al (this issue) with eighth-grade students with and without disabilities who wrote arguments about the scientific phenomena they were exploring. Although Monte-Sano et al (2021) makes no specific reference to dialogic teaching, her studies of teaching and learning history argue for the value of “disciplined inquiry” to support the preparation of citizens. Goldman et al’s (2016) description of “literary reading core constructs” includes “viewing literary texts as open to dialogue, privileging interrogating presumed authorial intent, valuing communities of readers who dialogue with one another within and across time” (p. 228).…”
Section: Theorizing the Dialogic In Argumentation And Literary Argumentmentioning
confidence: 99%